Relocation consequences on an ophthalmology consultation service from an inpatient to outpatient facility - Singh JS (Dove Medical Press, 2015)
Jorawer S Singh,1 Vincent M Imbrogno,2 Mary K Howard,3 Amandip S Cheema,3 Ausra D Selvadurai,4 Surbhi Bansal5 1Department of Ophthalmology, George Washington University, Washington, DC, 2Contemporary Ophthalmology of Erie, Erie, PA, 3Department of Ophthalmology, University at Buffalo, Buffalo, NY, 4OcuSight Eye Care Center, Rochester, NY, 5Department of Ophthalmology, Virginia Commonwealth University, Richmond, VA, USA Importance: This study shows that relocation of an academic ophthalmology residency program from an inpatient to an outpatient setting in western New York does not affect the consult volume but affects management patterns and follow-up rates.Objective: To investigate the effects on the ophthalmology consultation service of an academic program with relocation from a Regional Level-1 Trauma center to an outpatient facility.Design: Consultation notes from 3 years before and 3 years after the University at Buffalo’s (UB) Department of Ophthalmology relocation from a Regional Level-1 Trauma center (Erie County Medical Center) to an outpatient facility (Ross Eye Institute) were obtained from hospital electronic medical records and analyzed.Setting: Hospitalized care and institutional practice.Participants: All inpatient or Emergency Room Ophthalmology consultation patients from the Department of Ophthalmology at UB from 2004 to 2010 (1,379 patients).Exposures: None, this was a retrospective chart review.Main outcome measures: Patient demographics, reason for consult, diagnoses, and ophthalmic procedures performed by the UB Department of Ophthalmology before and after its relocation.Results: Relocation to the outpatient facility did not affect consult volume (P=0.15). The number of consults focusing on ophthalmic conditions, as a percentage of the yearly total, rose 460% (P=0.0001), while systemic condition consults with ocular manifestations fell 83% (P=0.0001). Consults for ocular trauma decreased 65% (P=0.0034). Consults ending with a diagnosis of “normal exam” fell, as a percentage of the yearly total (56%, P=0.0023), while diagnoses of new ocular conditions rose 17% (P=0.00065). The percentage of consults for Medicaid patients fell 12% (P=0.0001), while those for privately insured patients rose 15% (P=0.0001). The number of ophthalmic procedures did not change, but postconsult patient follow-up fell from 23% at the Erie County Medical Center clinic to 2% after the move to Ross Eye Institute, a ≥97% decrease.Conclusion and relevance: Relocation of UB’s academic Ophthalmology program from an inpatient department to an outpatient facility had no effect on its consultation patient or procedure volume, but it significantly affected the nature of consult diagnoses and decreased outpatient follow-up by >90% at the latter location. Many hospitals are creating separate outpatient facilities that may experience similar obstacles. Keywords: academic ophthalmology, ophthalmology consultation, relocation, resident education